Developing Pesantren Education Quality through Radicalism Prevention Program for Santri - Sadiah, Dewi (Jurnal Pendidikan Islam, 2022)
Pesantren (Islamic boarding schools) institutions in the current era are chosen for education destinations for the Muslim community to foster the quality of Islamic education, especially in countering ideas of religious radicalism. In this context, pesantren role in preventing radicalism are considered important to investigate. The present study investigates the education program carried out by pesantren in preventing radicalism. It was conducted at the Miftahul Huda Islamic Boarding School, Citangkolo, Banjar City. It applied qualitative approach using descriptive method. The data were collected using observation, in-depth interviews, and documentation. The results showed that the pesantren designs and delivers education using several dimensions including intellectual, skills, and character education. These three educational dimensions are implemented in classroom learning using various models, approaches, and learning strategies. For character building, education is supported by hidden curriculum. The curriculum is carried out in student activities according to the rules that is applied at pesantren. In pesantren, Kiai serves as a role model in education to boost all education program to develop santri character. Those education programs are used to prevent santri from radicalism in pesantren.